HUBUNGAN TINGKAT PENGETAHUAN TENTANG OLAHRAGA DENGAN MINAT BEROLAHRAGA PADA LANSIA DI POSYANDU LANSIA ‘AISYIYAH DESA SUMENGKO, KECAMATAN SUKOMORO KABUPATEN NGANJUK - Bagus Sasmito, Nanang; Rustanti, Elly; Kalimah, Siti (PRIMA WIYATA HEALTH, 2023)
Sports is a form of physical activity that has a good effect on the level of human physical ability if it is carried out correctly and with direction in the sense that its implementation has been calculated based on the limitations of the human body in facing physical workload and the excess of the human body in facing increasing stress (stress). The purpose of this study was to determine the relationship between the level of knowledge about sports and the interest in exercising among the elderly at the 'Aisyiyah Posyandu for the elderly in Sumengko Village, Sukomoro District, Nganjuk Regency. The design in this research is correlation with cross sectional approach. This research was conducted on September 12, 2020, with a population of 122 respondents, a sample of 30 respondents with a purposive sampling technique. The independent variables in this study are knowledge and the dependent variable interest in exercise in the elderly. Data collection using questionnaires, data analysis using the Spearman rank test with SPSS 17 at α = 0.05. The results of the study of 30 respondents, almost all respondents have good knowledge of sports, namely 27 respondents (90%). And the rest have enough interest in exercising, namely 3 respondents (10%). Based on the Spearman rank test, it was found that the p value = 0.000 at α = 0.05 and the value of r = 0.829. Because Ha ≤ α (0.05) then Ha is accepted Ho is rejected. There is a relationship between the level of knowledge and the interest in exercising among the elderly at the 'Aisyiyah Posyandu for the elderly in Sumengko Village, Sukomoro District, Nganjuk Regency, with a very close relationship. Increasing the knowledge of the elderly about the importance of exercising will certainly motivate the elderly to exercise regularly.